Forecasting by analogy on waste-to-energy technologies for future technology transfer in the Philippines some strategic dimensions - Hernandez, Diana Marie T. (Quezon City University of the Philippines Diliman, Technology Management Center, 2010)
The purpose of this study is to determine the key factors, which contribute to the success or failure of the technology transfer experience of waste-to-energy projects in the Philippines and how can these factors influence future and similar initiatives. It focuses on the case of Quezon City Controlled Disposal Facility Biogas Emission Reduction Project and of Montalban Landfill Methane Recovery and Power Generation Project, the pioneering international technology transfer projects in the country on waste-to-energy technology. A forecasting by analogy was adopted as the methodology to analyze the case of the Philippines vis-a-vis a specific waste-to-energy project in China, which also involved transfer of technology. The case in China was chosen as the "model" project by which the case of the Philippines was compared because of the similarity in the situation of the two such that both are developing countries at the time of the initiation of the project that they required technology transfer from international sources to acquire the necessary technology. The case in China also specifically highlighted the factors, which contribute to its partial success. Climate change is considered as one of the serious challenges that are being faced worldwide. Both natural processes and human activities, which contribute in the increase in greenhouse gases that leads to stronger greenhouse effect, can cause climate change. It has an impact not only environmentally but also socially, financially and economically. Since 1980, there have been various efforts, which were initiated to help address the issue of climate change. A recent initiative by most governments of the world is to adhere to an international agreement, the United Nations Framework Convention on Climate Change (UNFCC), which aims to stabilize greenhouse gas concentrations in the atmosphere at a level that would prevent dangerous, man-made interference with the climate system. An economic mechanism, the Clean Development Mechanism (CDM), which encouraged the cooperation between developed and developing countries to facilitate the achievement of targets set by the earlier agreement, has also been introduced. One of the popular strategies used recently to address climate change is the application of renewable energy as it is a low-carbon technology. The use of municipal solid waste as a renewable source to produce energy is an example of the application of renewable energy. This process helps reduce greenhouse gas emission and therefore contributes to addressing climate change. Since the technology required to derive renewable energy is relatively new, developing countries often opt to transfer the technology from international sources to acquire and use it in their countries. Philippines, a developing country in Southeast Asia, also has its share of significant initiatives to help address climate change. It has institutionalized several programs and projects to support the fight against the adverse effect of climate change. Earlier, the country in particular suffers from poor solid waste management due to rapidly growing population and lack of adequate disposal sites. To address such, the country has adopted laws to ensure that the local governments will be responsible in handling their municipal waste.
Two of the local government units in Metro Manila are hosting waste-to-energy projects, which are registered with the UNFCC and are currently benefiting from the CDM process. These projects do not only help address the problem of the country in waste management but these also contribute in addressing climate change by using a renewable energy process. The two pioneer waste-to-energy projects include the Quezon City Controlled Disposal Facility Biogas Emission Reduction Project implemented by the Pangea Green Energy Philippines and the Montalban Landfill Methane Recovery and Power Generation Project implemented by the Montalban Methane Power Corporation. Both projects involved a transfer of technology from international sources and are currently being operated by private companies, which have experience in the sector and which also provides full funding on all related activities. The members of the organization implementing the project have identified various factors, which contribute to the project success. Since the project started, the local governments where the projects are situated have already gained benefits such as preservation of environment, employment opportunities, income derived from royalties paid by the private companies, among others. The local government officials also take pride in hosting such pioneering waste-to-energy projects in the country within their community, which contribute in addressing climate change. The plant managers of the two projects ranked thirteen factors, which affect the transfer of waste-to-energy technology. The most important factors, which were identified are familiarity of the plant managers with the project operations, competence of the plant staffs, familiarity of the plant staffs with the project operation, competence of the plant manager, availability of funding to support the project, and introduction of carbon emission reduction credits as part of the CDM, which is a source of income for the company. The result of a further analysis show that following a forecasting by analogy technique, there are three main aspects by which the experience of the Philippines and China may be compared and analyzed. It includes partnership and communication, technical requirements of the project, and availability of additional incentives in undertaking the project. The experience of the two countries showed that the international technology transfer process has benefited both countries in a number of ways. However, there have also been challenges along the way, which they had to resolve to facilitate the successful implementation of the project. The findings of this study will serve as a useful input to substantiate further studies in the sector such as a roadmapping technique or a scenario building process. With the growing interest to initiate projects of similar nature in other local governments across the country, it may be noteworthy to consider and examine the experience of Quezon City and Rodriguez, Rizal in planning for their own projects. In this way, they will be able to learn from the lessons generated as a result of the challenges experienced by the two pioneer projects and hopefully will have better results and be also successful in contributing in the battle against climate change.
In partial fulfillment of the requirements in TM 299.2
Thesis
Keywords: Sustainable energy sources; Sustainability